Electrical properties of polyethylene/polypropylene compounds for high-voltage insulation - Sameh Ziad Ahmed Dabbak; Hazlee Azil Illias; Ang, Bee Chin; Nurul Ain Abdul Latiff; Mohamad Zul Hilmey Makmud (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
In high-voltage insulation systems, the most commonly used material is polymeric material because of its high dielectric strength, high resistivity, and low dielectric loss in addition to good chemical and mechanical properties. In this work, various polymer compounds were prepared, consisting of low-density polyethylene (LDPE), high-density polyethylene (HDPE), polypropylene (PP), HDPE/PP, and LDPE/PP polymer blends. The relative permittivity and breakdown strength of each sample types were evaluated. In order to determine the physical properties of the prepared samples, the samples were also characterized using differential scanning calorimetry (DSC). The results showed that the dielectric constant of PP increased with the increase of HDPE and LDPE content. The breakdown measurement data for all samples were analyzed using the cumulative probability plot of Weibull distribution. From the acquired results, it was found that the dielectric strengths of LDPE and HDPE were higher than that of PP. Consequently, the addition of LDPE and HDPE to PP increased the breakdown strength of PP, but a variation in the weight ratio (30%, 50% and 70%) did not change significantly the breakdown strength. The DSC measurements showed two exothermic crystallization peaks representing two crystalline phases. In addition, the DSC results showed that the blended samples were physically bonded, and no co-crystallization occurred in the produced blends.